Utilization of Sociometrics in Protocol Communication Mapping in Higher Education Organizations - Delvira Nurul Aini Yuliandari Harahap; Teguh Priyo Sadono; Merry Fridha Tri Palupi (Riviera Publishing, 2025)
This study examines the organizational communication network within the Surabaya Education Foundation of August 17, 1945 (YPTA Surabaya), particularly focusing on its protocol unit, which manages ceremonial activities and institutional relations. Given the complexity of the structure and the intensity of official activities, a structured and efficient communication network is essential. Using a sociometrics-based communication audit approach, the research maps the communication network of the protocol and assesses its effectiveness. The research method involves a descriptive qualitative case study, with data collected through observation, in-depth interviews, and documentation. Sociometric analysis is employed to visualize relationships through sociograms, identifying key communication nodes, dominant actors, and those less involved in the flow of information. The findings reveal a centralized communication network, heavily reliant on a few key individuals as the main conduits for information. Informal communication patterns dominate coordination, leading to potential message distortion and coordination issues. The study concludes that the protocol’s effectiveness is significantly impacted by the uneven communication structure and recommends strengthening the network with formal communication mechanisms, clearer SOPs, and enhanced coordination within the protocol unit. This research contributes to the development of communication audit studies in educational organizations and offers insights into sociometrics-based network mapping.